Carrier-Free, Dual-Functional Nanorods Via Self-Assembly Of Pure Drug Molecules For Synergistic Chemo-Photodynamic Therapy - Zhao Y (Dove Medical Press, 2019)
Yuping Zhao,1,* Yanna Zhao,1,* Qisan Ma,1 Bin Sun,1 Qingpeng Wang,1 Zhuang Ding,1 Huaizhen Zhang,2 Xiuling Chu,3 Min Liu,1 Zhengping Wang,1 Jun Han1 1Institute of Biopharmaceutical Research, Liaocheng University, Liaocheng, Shandong 252059, People’s Republic of China; 2School of Environment and Planning, Liaocheng University, Liaocheng, Shandong 252059, People’s Republic of China; 3College of Agriculture, Liaocheng University, Liaocheng, Shandong 252059, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanna Zhao; Jun HanInstitute of Biopharmaceutical Research, Liaocheng University, Liaocheng 252059, Shandong Province, People’s Republic of ChinaFax +86 635 8239136Email ynzhao2011@163.com; junhanmail@163.comBackground: The combination of chemo-photodynamic therapy based on nano-technology has emerged as a preferable and promising measure for synergetic antitumor therapy.Purpose: The aim of this study was expected to overcome most of the safety concerns from nano-carriers and improve the chemo-photodynamic synergistic antitumor efficacy.Methods: Herein, we reported a facile and effective approach based on the self-assembly of chemotherapeutic agent 10-hydroxycamptothecin (HCPT) and photosensitizer chlorin e6 (Ce6) for preparing stably dual-functional nanorods (NRs).Results: The chemical thermodynamic parameters obtained from isothermal titration calorimeter (ITC) and the microcosmic configuration snapshots acquired by molecular dynamics (MD) simulations verified that HCPT and Ce6 molecules tended to assemble with each other through various intermolecular forces. The as-prepared HCPT/Ce6 NRs possessed a relatively uniform size of around 165 nm and zeta potential of about −29 mV, together with good stability in aqueous solution and freeze-dried state. In addition, both the extra- and intracellular reactive oxygen species (ROS) generation capacity of the NRs under laser irradiation was significantly enhanced compared with Ce6 injections. Moreover, the dual-functional HCPT/Ce6 NRs exhibited a substantial in vitro/in vivo synergistic antitumor efficacy under laser irradiation due to the integration of the two therapeutic modalities into one drug delivery system. Besides, no obvious hepatic or renal toxicity was observed in the NRs treatment groups.Conclusion: Taken together, HCPT/Ce6 NRs demonstrated a powerful efficacy in chemo-photodynamic therapy for breast cancer. Therefore, the carrier-free dual-functional NRs prepared in a facile and effective strategy might give inspiration for the development of combined antitumor therapy.Keywords: carrier-free, self-assembly, chemo-photodynamic, dual-functional nanorods, combined antitumor therapy, synergistic antitumor efficacy